65‐2: Red Electroluminescence Quantum Dot Devices (EL‐QD) with Improved Efficiency and Lifetime. Issue 1 (28th June 2021) - Park, Myoungjin; Kim, Heung Gyu; Kang, Jin-goo; Ha, Jaekook; Lee, Changhee
Abstract : By optimizing the interface between charge transport layer and quantum dots in EL‐QD devices based on InP QDs, 1.4‐fold improvement in the efficiency and 3‐fold increasing lifetime are obtained.